Rural, urban and suburban differences in the prevalence of metabolic syndrome in individuals aged ≥50 years in Northwest China - Jiao, Yang; Zhang, Chunhong; Ming, Jie; Xu, Shaoyong; Wang, Yangwei; Yao, Xiaoli; Jia, Aihua; Li, Hui; Sui, Jing; Qin, Jianjun; Li, Wenjie; Zhang, Haixiong; et al. (Frontiers in Public Health, 2025)
BackgroundMetabolic syndrome (MetS) is a significant risk factor for type 2 diabetes and cardiovascular disease. The aim of this study was to identify the characteristics of MetS in northwest China.MethodsThree thousand and one adults were included (1,915 females, 1,086 males). The prevalence of MetS analysis was stratified according to gender, age and the region of residence.ResultsMetS prevalence in females and males was 49.7 ± 9.8% and 32.0 ± 9.0%, respectively (p < 0.001). MetS prevalence in females increased with age and was greater in rural (n = 217) females (53.6%) compared to urban (n = 754) (45.5%) or suburban (n = 818) females (52.0%) (p = 0.003). Regression analysis revealed that rural region, age, half-meat and half-vegetable dietary style, never dieted, weight increase in the previous year and a family history of high blood pressure were independent risk factors for the development of MetS, particularly in women aged ≥50 years.ConclusionMetS prevalence in women was greater than for men, increased with age and occurred more frequently in rural compared to urban and suburban females.